The powerful presence of the past : integration and conflict along the upper Guinea Coast - Knörr, Jacqueline, 1960-; Trajano Filho, Wilson (African social studies series ;, 2010)
This book conceptualizes integration and conflict as interrelated dimensions of social interaction, social relationships and alliances, identifications and identity constructions within society at large. In order to reach an in-depth understanding of integrative and violent forms of interaction in the region of the Upper Guinea Coast, authors take into account the impact and repercussions of specific historical experiences as well as the continuities and changes of social patterns affected by the interaction of local and globalized values, institutions, and models of social organization. Rathe.